Lacosamide for the treatment of partial-onset seizures. (June 2012) - Biton, Victor
Lacosamide (LCM) is an antiepileptic drug approved as adjunctive therapy for partial-onset seizures in adults. It has a mechanism of action that differs from other antiepileptic drugs in that it selectively enhances sodium channel slow inactivation, which is in contrast to 'traditional' sodium channel blockers (e.g., carbamazepine, oxcarbazepine, lamotrigine and phenytoin) that primarily affect fast inactivation. The pharmacokinetic profile of LCM is well characterized and includes a fast rate of absorption, little or no interaction with cytochrome P450 isoenzymes, limited effect of age and gender on plasma levels, and low potential for drug–drug interactions. Safety and efficacy data from three double-blind, placebo-controlled trials, as well as pooled and post hoc analyses of these three trials, have been published, and demonstrate the safety and rapid-onset efficacy of LCM in adults with treatment-refractory partial-onset seizures. LCM is available in tablets and an intravenous formulation when oral administration is temporarily not feasible.